Implementasi Mediasi Elektronik dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Purwodadi: Study tentang Pasca Berlakunya Peraturan Mahkamah Agung Nomor 3 Tahun 2022 - Ahmad Khoirul Amin; Sigit Wibowo; Lucia Setyawahyuningtyas (Jurnal Hukum Caraka Justitia, 2026)
This research seeks to evaluate the application and identify the obstacles associated with electronic mediation (e-mediation) in handling divorce proceedings at the Purwodadi Religious Court. After the introduction of Supreme Court Regulation (PERMA) Number 3 of 2022 regarding Electronic Mediation in Courts, the Purwodadi Religious Court has started to apply e-mediation as a method for resolving disputes, which is viewed as more adaptable and effective. This research adopts a normative juridical framework utilizing a legal perspective and case analyses. Information was gathered via document analysis (including PERMA, court documentation, and case records), comprehensive interviews with judges, mediators, and parties involved, along with direct observation at the Purwodadi Religious Court. The findings from this analysis indicate that the execution of electronic mediation has been conducted in alignment with the guidelines set forth in PERMA No. 3 of 2022, with a success rate of reaching a peaceful agreement of 36.3% of 215 cases in the 2023-2025 period. E-mediation has been proven to increase efficiency by shortening the average settlement time to 25 days and expanding access for parties with distance constraints. However, this implementation faces technical obstacles (internet infrastructure, digital literacy), non-technical (difficulties in building rapport, face-to-face preferences), and administrative obstacles (lack of detailed internal SOPs).